Spatio-temporal dynamics and transition from asymptotic equilibrium to bounded oscillations in Chrysomya albiceps (Diptera, Calliphoridae) - Godoy, Wesley Augusto Conde [UNESP]; Von Zuben, Fernando José; Von Zuben, Claudio José [UNESP]; Reis, Sérgio Furtado dos [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2001)
The sensitivity of parameters that govern the stability of population size in Chrysomya albiceps and describe its spatial dynamics was evaluated in this study. The dynamics was modeled using a density-dependent model of population growth. Our simulations show that variation in fecundity and mainly in survival has marked effect on the dynamics and indicates the possibility of transitions from one-point equilibrium to bounded oscillations. C. albiceps exhibits a two-point limit cycle, but the introduction of diffusive dispersal induces an evident qualitative shift from two-point limit cycle to a one fixed-point dynamics. Population dynamics of C. albiceps is here compared to dynamics of Cochliomyia macellaria, C. megacephala and C. putoria.
Keywords: spatial dynamics; sensitivity analysis; Chrysomya albiceps